Pengaruh Model Pembelajaran Problem Based Learning (PBL) dan Kreativitas Belajar terhadap Hasil Belajar Kelas X Jurusan Bisnis Ritel SMK Negeri 1 Patumbak - Putri Sianturi; Muhammad Fitri Rahmadana (ARZUSIN, 2026)
Although the low student learning outcomes in the subject Fundamentals of the Marketing Skills Program in Grade X of the Retail Business Department at SMK Negeri 1 Patumbak remain a concern, the use of less varied learning models and differences in levels of learning creativity are presumed to be factors influencing this condition. This study aimed to analyze the effect of the Problem Based Learning (PBL) model and learning creativity on student learning outcomes. This study used a quantitative approach with an experimental design involving an experimental class and a control class. The population of the study consisted of all Grade X students in the Retail Business Department at SMK Negeri 1 Patumbak, with the sampling technique using total sampling. Data were collected through learning outcome tests and learning creativity questionnaires, and were then analyzed using the t-test and linear regression with the assistance of the SPSS program. The results showed that the Problem Based Learning model had a positive and significant effect on student learning outcomes compared with conventional learning. In addition, learning creativity was also proven to have a positive and significant effect on student learning outcomes. Simultaneously, the Problem Based Learning model and learning creativity contributed to improving student learning outcomes. Thus, this study confirms that the implementation of the Problem Based Learning model supported by student learning creativity can improve learning outcomes more optimally. These findings contribute to strengthening innovative learning practices in vocational education and have practical implications for teachers to apply more varied learning models and encourage student creativity in order to improve the quality of learning outcomes.